Sosialisasi : Strategi Akademik Meningkatkan Peringkat Sinta Score Overall (SSO) - Eko Sudarmanto; Harimurti Wulandjani; Jennifer Farihatul Bait; Muhammad Abdul Rosid; Budi Rohmansyah; Daniel Rahandri; Abdul Karim (Lembaga Pengembangan Kinerja Dosen, 2025)
The Sinta Score Overall (SSO) ranking is a crucial indicator in assessing the academic quality and productivity of lecturers and researchers. However, many academics face challenges in improving their SSO ranking due to a lack of understanding of effective strategies for scientific publication. Therefore, this community service initiative was conducted through a national webinar with the primary objective of providing insights and strategies to academics on how to optimize their SSO. The method employed in this initiative involved dissemination and interactive discussions via a webinar platform, featuring speakers with extensive experience in scientific publication and Sinta ranking. The webinar covered key topics, including high-quality publication strategies, the importance of international collaboration, and the utilization of academic media to enhance research visibility. The results indicate that improving publication quality, expanding collaborative networks, and selecting research topics aligned with global issues are essential steps in increasing SSO. By implementing the right strategies and maintaining consistency in scientific publication, academics can enhance their reputation and expand research collaboration opportunities.